199 Changes in natalizumab exposure and PML incidence over time. Issue 12 (14th November 2019) - Giovannoni, Gavin; Kappos, Ludwig; Berger, Joseph; Cutter, Gary; Fox, Robert; Wiendl, Heinz; Chang, Ih; Kasliwal, Rachna; Lee, Lily
Abstract : Introduction: Since the identification in 2012 of three risk factors for natalizumab-associated progressive multifocal leukoencephalopathy (PML), changes in the PML incidence rate have been of interest. Methods: The incidence of confirmed PML cases in Biogen's postmarketing global safety database from November 2009 to November 2017 was evaluated retrospectively. Overall incidence in natalizumab-exposed patients was determined by the estimated total number of patients exposed and the number of confirmed cases. Changes in exposure patterns over time were evaluated by 12-infusion epochs. Results: As of 30 November 2017, 180, 656 patients worldwide had received ≥1 dose; overall natalizumab-associated PML incidence was 4.19/1000 patients. Since mid-2016, overall monthly incidence of PML appears to have stabilised, remaining between 4.18 and 4.24/1000. PML incidence was greatest in later, higher risk infusion epochs (≥37 infusions). The relative increase in the proportion of patients in higher-exposure epochs (>24 infusions) has declined from 2013 to 2017. Conclusions: The stabilisation of overall natalizumab-associated PML incidence beginning mid-2016 coincides with the introduction of a new risk algorithm, suggesting that risk stratification factors are being incorporated into clinical practice and may continue to impact future incidence. Support: Biogen. Disclosures to be included on poster.